Pelatihan Daring Cara Edit Video Mudah dan Menarik untuk Memaksimalkan Pembelajaran Siswa Tingkat Pre-School - Meriska Defriani; Mochzen Gito Resmi; Dede Irmayanti (Jurnal Abdimas Adpi Sosial dan Humaniora, 2020)
Sekolah Alam Purwakarta (SAP) is a school that integrates four pillars of education, namely the pillars of faith, knowledge, leadership, and entrepreneurship. SAP not only emphasizes on achieving academic goals but also on developing life skills. In addition, SAP uses a national curriculum which was later developed so as to make the universe and local potential a source of learning, learning media, and classrooms. During the Covid-19 pandemic, pre-school level student learning is almost entirely done at home with guidance in the form of assignments that have been prepared by the facilitator. Each task given aims to develop students' cognitive, motoric, or affective. Every task that has been done must be submitted with documentation by the parents to the facilitator as a daily assessment. To get good documentation, parents can use photos or videos as media. Therefore, video editing training needs to be done to maximize the learning process of pre-school students in SAP. This activity is carried out by providing online training to facilitators and parents of pre-school level students in SAP. This training was carried out for 120 minutes and was attended by 8 facilitators and 20 parents. At the end of the activity, the facilitator makes an example of a learning video while the parents make an example of a video of their child's assignment portfolio. With the implementation of this training, facilitators and parents have the ability to edit videos so they can maximize the learning of pre-school level students in SAP.